Beware: Gastrointestinal symptoms can be a manifestation of COVID-19 - M. Schmulson; M.F. Dávalos; J. Berumen (Revista de Gastroenterología de México (English Edition), 2020)
Background: There is a growing number of reports of COVID-19 cases presenting gastrointestinal (GI) symptoms. Aims: To review studies reporting GI symptoms among COVID-19 patients. Results: Fifteen papers (2800 patients) were identified. Frequency of GI symptoms varied from 3.0% to 39.6%, including diarrhea: 7.5%, nausea: 4.5%, anorexia: 4.4%, vomiting: 1.3%, abdominal pain: 0.5%, belching/reflux: 0.3%. These may be the first manifestation of COVID-19, however, there is controversy whether these reflect better or worst prognosis. Finally, the potential relationship with the angiotensin converting enzyme 2 (ACE2) cell receptor in the digestive tract as the virus entry route, is discussed. Conclusions: GI symptoms may be common in COVID-19 and may be the first manifestation before fever and respiratory symptoms. Therefore, clinicians and gastroenterologists need to be aware of these atypical cases during the current pandemic and of the fecal–oral transmission, and preventive measures may be implemented. Resumen: Antecedentes: Existe un incremento de reportes sobre casos del COVID-19 que presentan síntomas gastrointestinales (GI). Objetivo: Revisión de estudios que reportaron síntomas GI en COVID-19. Resultados: Quince artículos (2800 pacientes) fueron identificados. La frecuencia de síntomas GI varió del 3.0 al 39.6%, incluyendo diarrea: 7.5%, náuseas: 4.5%, anorexia: 4.4%, vómito: 1.3%, dolor abdominal: 0.5% y eructos/reflujo: 0.3%. Estos pueden ser la primera manifestación de COVID-19, pero existe controversia sobre si reflejan mejor o peor pronóstico. Se discute la relación potencial del receptor de la enzima convertidora de la angiotensina 2 (ACE2) en el tracto digestivo como ruta de entrada del virus. Conclusión: Los síntomas GI pueden ser comunes en COVID-19 y ser la primera manifestación, incluso antes de fiebre y síntomas respiratorios. Por ello, los clínicos y gastroenterólogos debemos estar alerta a estos casos atípicos durante la actual pandemia y sobre la probable transmisión fecal-oral, y considerar medidas preventivas.